2022
DOI: 10.1186/s12985-022-01835-w
|View full text |Cite
|
Sign up to set email alerts
|

Pooled prevalence and genetic diversity of norovirus in Africa: a systematic review and meta-analysis

Abstract: Background Noroviruses are the leading cause of acute gastroenteritis in all age groups globally. The problem is magnified in developing countries including Africa. These viruses are highly prevalent with high genetic diversity and fast evolution rates. With this dynamicity, there are no recent review in the past five years in Africa. Therefore, this review and meta-analysis aimed to assess the prevalence and genetic diversity of noroviruses in Africa and tried to address the change in the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 60 publications
13
23
0
Order By: Relevance
“…Similar to the RdRp genotypes, GII.4 was the dominant genotype based on the VP1 region. This is consistent with previous studies in Nigeria [ 21 , 23 ] and elsewhere globally [ 18 ]. This finding further corroborates the predominant widespread distribution of the GII.4 genotype over other GII genotypes.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Similar to the RdRp genotypes, GII.4 was the dominant genotype based on the VP1 region. This is consistent with previous studies in Nigeria [ 21 , 23 ] and elsewhere globally [ 18 ]. This finding further corroborates the predominant widespread distribution of the GII.4 genotype over other GII genotypes.…”
Section: Discussionsupporting
confidence: 94%
“…Globally, viral gastroenteritis is still a public health issue, and NoV is significantly responsible for outbreaks and sporadic cases. The NoV detection rates of 5.1% and 2.3%, based on RdRp and VP1 regions, respectively, were lower than those reported in some earlier studies in Nigeria [ 21 , 22 , 23 , 24 , 25 ], and the pooled prevalence of 19.25% in Africa between 2015 and 2021 [ 18 ]. The observed discrepancy might be due to geographical location, sample size, study population, and varying diagnostic methods.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…We demonstrated that NVII is an important pathogen among infants seeking medical care with MSD in sub-Saharan Africa. Our findings corroborate and extend observations by others regarding the predominance of the NVII genogroup in Africa [ 25 ], and that circa 70% of pediatric norovirus diarrhea cases occur between age 6 and 23 months [ 26 ], commonly peaking between 6 and 11 months [ 11 ].…”
Section: Discussionsupporting
confidence: 92%